The True Heart: Sylvia Townsend Warner's impolitics of love. Issue 7 (3rd July 2022) - Schaller, Karen Ann
ABSTRACT: What can Sylvia Townsend Warner teach literary criticism about love? Despite critical neglect for this twentieth-century British writer, I argue that Warner's work can help us think about how we read love. Debates about Warner's significance persistently involve, and revolve around, her writing of love and its revolutionary potential. But if her love plots offer her readers the hope of a transformational politics, its expressions also invoke critical discomfort, even shame: to love Warner is to love a writer whose politics of love also engage attachments to imperialism, to eugenics, and to difficult discourses of race and class. If these ugly adjacencies disrupt recuperative readings that put love's potential at the heart of their critical projects, however, this tells us there is a politics of love at work not only in Warner's writing, but in the very critical narratives we bring to her work. Whether or not we are Warner scholars doesn't matter: critical attachments to love's potential are not limited to Warner's moment, but alive in our own.